Attention-deficit hyperactivity disorder: preventing overdiagnosis and overtreatment - Jean-Cla (Sociedade Brasileira de Medicina de Família e Comunidade, 2015)
The first part of this article focuses on the wide variations in the diagnosis of attention-deficit hyperactivity disorder (ADHD) that are observed between countries and between regions within the same country. Diagnosing ADHD is more problematic than is commonly thought. For instance, younger American children in the same grade at school are 64% more likely to receive the diagnosis; symptoms can result from many underlying causes. Furthermore, ADHD can be confused with many other health issues. As a result it is largely overdiagnosed and overtreated. The second part of the article reviews recent studies showing that anti-ADHD drugs lack long-term effectiveness and come with important adverse events. Overall, and in the long run, the pharmacologic treatment of ADHD is likely to cause more harm than good.